My Voice - Alterman, Ike 1928- (My voice:, 2024)
"Ike Alterman was born in 1928 in Ozarów in Poland. In telling his story, he recounts his happy Orthodox Jewish upbringing, the tragic loss of his immediate family in Treblinka and Auschwitz, his ordeal through concentration camps including Auschwitz-Birkenau, surviving multiple death marches, and his liberation in Theresienstadt in 1945. Ike is one of 'The Boys', brought to Windermere in England, as part of a British governmental scheme granting asylum to Holocaust child survivors. Ike describes his rehabilitation, and new life in Manchester, where he started a family and established a jewellery business. Later in life, Ike pursued closure by revisiting his hometown in Poland and undertaking a difficult trip to Treblinka. He reflects on his life after immeasurable loss, and what it means to endure and bear witness. Ike's book is part of the My Voice book collection, a stand-alone project of The Fed, the leading Jewish social care charity in Manchester, dedicated to preserving the life stories of Holocaust survivors and refugees from Nazi persecution who settled in the UK. The oral history, which is recorded and transcribed, captures their entire lives from before, during and after the war years. The books are written in the words of the survivor so that future generations can always hear their voice. The My Voice book collection is a valuable resource for Holocaust awareness and education."